Associations of volume and other hospital characteristics on mortality within 30 days of acute myocardial infarction in South Korea. Issue 11 (6th November 2015) - Han, Kyu-Tae; Kim, Sun Jung; Kim, Woorim; Jang, Sung-In; Yoo, Ki-Bong; Lee, Seo Yoon; Park, Eun-Cheol
Abstract : Objective: The mortality for acute myocardial infarction (AMI) has declined worldwide. However, improvements in care for AMI in South Korea have lagged slightly behind those in other countries. Therefore, it is important to investigate how factors such as hospital volume, structural characteristics of hospital and hospital staffing level affect 30-day mortality due to AMI in South Korea. Setting: We used health insurance claim data from 114 hospitals to analyse 30-day mortality for AMI. Participants: These data consisted of 19 638 hospitalisations during 2010–2013. Interventions: No interventions were made. Outcome measure: Multilevel models were analysed to examine the association between the 30-day mortality and inpatient and hospital level variables. Results: In the 30 days after hospitalisation, 10.5% of patients with AMI died. Hospitalisation cases at hospitals with a higher AMI volume had generally inverse associations with 30-day mortality (1st quartile=ref; 2nd quartile=OR 0.811, 95% CI 0.658 to 0.998, 3rd quartile=OR 0.648, 95% CI 0.500 to 0.840, 4th quartile=OR 0.807, 95% CI 0.573 to 1.138). In addition, hospitals with a greater proportion of specialists were associated with better outcomes (above median=OR 0.789, 95% CI 0.663 to 0.940). Conclusions: Health policymakers need to include volume and staffing when defining the framework for treatment of AMI in South Korean hospitals. Otherwise, they must consider increasing the proportion of specialists or regulating the hiring of emergency medicine specialists. In conclusion, they must make an effort to reduce 30-day mortality following AMI based on such considerations.